A child information protection scheme based on hyperchaotic mapping - Tu, Chenchen; Niu, Li; Cui, Rongrong (Frontiers in Physics, 2025)
This paper proposes an encryption scheme based on hyperchaotic mapping for child information protection. First, phase diagrams of the hyperchaotic mapping are plotted under different parameter combinations, and the variation in phase trajectories confirms the sensitivity of the hyperchaotic mapping to control parameters. Then, the hyperchaotic mapping is iterated to obtain chaotic sequences, and the chaotic sequences are quantized to obtain pseudo-random sequences. Finally, based on those, a scrambling algorithm and a diffusion algorithm are designed to encrypt and protect the images. The original images are scrambled and diffused to obtain the ciphertext images and used to protect the information of missing children, which can effectively protect the safety of children’s information and assist the public security bureaus to quickly contact the parents of missing children.